New species of water mites from the Comoros (Acari: Hydrachnidia) - Smit, Harry; Pesic, Vladimir; Mary-Sasal, Nathalie (Zootaxa, 2009)
Three new species are described from the Comoros, an archipelago in the Indian Ocean: Teratothyasides scutulatus Smit & Pesic n. sp., Platymamersopsis comoros Smit & Pesic n. sp. and Atractides comorosensis Smit & Pesic n. sp. One species is reported new for the fauna of the Comoros, i.e. Monatractides ventriosa (K. Viets, 1916).